2017
DOI: 10.1097/mol.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E metabolism and functions in brain and its role in Alzheimer's disease

Abstract: Purpose of reviewAPOE4 genotype is the strongest genetic risk factor for Alzheimer's disease. Prevailing evidence suggests that amyloid β plays a critical role in Alzheimer's disease. The objective of this article is to review the recent findings about the metabolism of apolipoprotein E (ApoE) and amyloid β and other possible mechanisms by which ApoE contributes to the pathogenesis of Alzheimer's disease.Recent findingsApoE isoforms have differential effects on amyloid β metabolism. Recent studies demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 54 publications
(86 reference statements)
1
100
0
Order By: Relevance
“…LXRs and the genes regulated by LXRs such as ABCA1, ABCG1 and APOE, modulate intracellular cholesterol content and cholesterol efflux and have been associated with AD pathogenesis 42 . Our analysis also identified PPARA as putative regulator of ABCA1 and recent studies have demonstrated that PPAR pathway activation increased ABCA1 levels, that in turn lead to APOE lipidation and amyloid ß clearance 43 . We also identified transport of taurine as an important factor from the metabolic analysis.…”
Section: Transcriptional Regulation Of Bile Acid and Cholesterol Genessupporting
confidence: 65%
“…LXRs and the genes regulated by LXRs such as ABCA1, ABCG1 and APOE, modulate intracellular cholesterol content and cholesterol efflux and have been associated with AD pathogenesis 42 . Our analysis also identified PPARA as putative regulator of ABCA1 and recent studies have demonstrated that PPAR pathway activation increased ABCA1 levels, that in turn lead to APOE lipidation and amyloid ß clearance 43 . We also identified transport of taurine as an important factor from the metabolic analysis.…”
Section: Transcriptional Regulation Of Bile Acid and Cholesterol Genessupporting
confidence: 65%
“…We identified a unique cell type-specific signal between microglia and genetic variants associated with High-density lipoprotein (HDL) cholesterol level (q MAGMA = 0.046) (Figure 2a). Given the role of lipids in AD 15,16 , we asked whether the HDL cholesterol association was related to the association between AD risk and microglia gene expression (Figure 2a). However, conditional analysis suggests distinct genetics underlie the associations of AD and HDL cholesterol levels with microglia ( Supplementary Figure 8).…”
Section: The Single-cell Profiles Of the Substantia Nigra Inform On Tmentioning
confidence: 99%
“…Moreover, the single amino acid difference coded by APOE ε2, ε3 and ε4 alleles affects the structures of apoE isoforms and influence their ability to bind lipids, receptors, and Aβ [37]. Aβ accumulation in human brain follows the pattern of APOE ε4 > APOE ε3 > APOE ε2 [41] and Aβ clearance is promoted by lipidation of apoE [38]. In addition to preventing Aβ oligomer formation and inducing Aβ degradation, lipidated apoE promotes Aβ efflux via blood‐brain barrier and might enhance peripheral clearance through apoE‐containing HDL particles [38].…”
Section: Apoe Isoforms and Phospholipidsmentioning
confidence: 99%
“…APOE ε3 . APOE ε2 [41] and Ab clearance is promoted by lipidation of apoE [38]. In addition to preventing Ab oligomer formation and inducing Ab degradation, lipidated apoE promotes Ab efflux via bloodbrain barrier and might enhance peripheral clearance through apoE-containing HDL particles [38].…”
Section: Apoe Isoforms and Phospholipidsmentioning
confidence: 99%